Analisis Determinan Keputusan Perusahaan Melakukan Transfer Pricing - Rita Wijayanti (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2020)
This study aims to analyze the effect of intangible assets, taxes, tunneling incentives, and bonus mechanisms on the company's decision to transfer pricing. This study uses secondary data available on the company's annual financial statements and can be accessed on the Indonesia Stock Exchange's website. The research population is manufacturing companies listed on the Indonesia Stock Exchange in the period 2013-2017. The sampling technique is done by using purposive sampling method, which produces a final sample of 112. The analytical method used is logistic regression analysis. The results of the analysis in this study indicate that tax variables have a positive effect on corporate transfer pricing decisions, while the other three variables such as intangible assets, tunneling incentives, and bonus mechanisms do not affect the company's decision to transfer pricing.